THE FREQUENCY OF 'OFTEN' - Little, Arthur S. (The Accounting Review, 1947)
Abstract The article presents information regarding laws and legislation related to accounting procedures in savings and investments. In 1908, the State of New York Legislature, enacted laws which in effect and intent required savings banks and insurance companies to put bond purchases on the books at cost and thereafter to make correct entries as coupons. There was much opposition from the densely populated group in banking and accounting circles who never forget anything and never learn anything and even after the law had been in more or less successful operation for about two years a prominent Wall Street oracle, in a Bankers' Convention speech, denounced the whole scheme as "a delusion and a snare" and about the same time the "Commercial & Financial Chronicle," editorially attributed the existence of said law to the influence of "an evil genius" that had arisen. But the first important thing that happened almost immediately alter the enactment of the "Amortization Law" was a decree from the Banking & Insurance Commissioners at Albany, New York, whereby they catered to the lazy and ignorant by authorizing, if desired, the use of the "pro-rata method" instead of the correct one.